Upper Devonian "griottes" facies of the Ben-Zireg area (Bechar Basin, southwestern Algeria): Stratigraphy, microfacies analysis and paleo-environmental reconstruction. (December 2022) - Abbache, Abdelkader; Ouali Mehadji, Abdelkader; Allaire, Ninon; Monnet, Claude; Crônier, Catherine; Zaagane, Mansour; Fetati, Aicha
Abstract: The widespread 'griotte' facies of the Late Devonian (Frasnian to Famennian) in the Ben-Zireg area of the Bechar basin (Southwestern Algeria) is described here from three sections (BZI, BZII and BZIII) which have been sampled bed-by-bed from the 'Griotte' limestone of the Ben-Zireg Formation. Based on macro- and microfacies analysis, this formation has been divided into three members: the Lower Member consists of 'griotte' limestone, the Median Member consists of clayey-limestone 'griotte', and the Upper Member consists of shales with intercalations of 'griotte' limestone. The ammonoid specimens recolted in this formation allow to characterize three Late Devonian biozones: the Cheiloceras Zone (UD II) of Early Famennian, the Gonioclymenia (UD V) and the Kalloclymenia (UD VI) zones of Late Famennian. Based on the field observations and the analysis of 270 thin sections, six microfacies types (MFT-1 to MFT-6) have been identified. They are dominated by biomicritic wackestones and mudstones characterizing a quiet marine environment corresponding to a distal ramp with deposits containing tempestites echoes and internalites fine grained supplies. Highlights: The Late Devonian griotte facies of Ben Zireg developed in a carbonate platform. Three ammonoids zones are identified: (UD II), (UD V) and (UD VI). The lithological dominant characters are nodular structures. Six microfacies types dominated by biomicritic wackestone-mudstone of distal ramp.